PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIC SD NEGERI 017 SEDINGINAN KECAMATAN TANAH PUTIH - Yulihasmi Yulihasmi; munjiatun munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is a class act that is agains the background of the low learning outcomes of social science students in grade 017 public elementary schools IIIC districts Sedinginan white ground academic year 2014/2015. With rat average 65,12% while the value of the minimum completeness criteria is 70 ips. Of 16 students only 7 students who achieve a minimum completeness criteria with classical completeness 43,75 %. This research was conducted on 16 March until 28 April 2015 by two cycle. This research subject is class IIIC country districts Sedinginan white ground with a number of students 16 people, consists of 5 men and 11 female. Formulation of the problem in this study is whether the application of the model of the type of snowball throwing kooperatif can improve learning outcomes social sciences graders IIIC SD 017 countries Sedinginan ground white districts. Research data show that the process of learning and learning outcomes has increased. This can be proved on the activity sheet teacher in the learning process in the firt cycle of the firs meeting enough category and 58,3 % second meeting me increased to 72,2% with the good category. Two cycle of the first meeting 86,1% verygood category and the second meeting increased 94,4% with verygood category. Data analysis of student activity sheet in cycle the first meeting enough category and 55,5% second meeting increased to 61,1% good category,at the first meeting of the second meeting increased to 91,6% with verygood category. Student learning outcomes also increased. Learning outcomes prior to action by an average 65,12 an increased in the daily tests. One with an average to 72,5% with the percentage of 11,33% the two daily tests increased with 86,56% average rat percentage 32,92%. Study show that implementation of cooperative learning model snowball throwing can improve learning outcomes of science social graders IIIC public lementary school districts Sedinginan white ground.Key words : Cooperative learning model Snowball Throwing and social science learning outcomes